PENGARUH KOMPENSASI, MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN BAGIAN AKUNTANSI (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI SURABAYA) - Windy Aprilia Murty; Gunasti Hudiwinarsih (STIE Perbanas Surabaya, 2012)
The era of globalization encourages companies to self-improvement in order to compete andretain its life. The presence of a strategic plan is required to implement them. Therefore, therole of accounting in a company is indispensable in terms of decision making. Employees ofthe accounting department tend to have high job stress as part of their time is spent in theworkplace and in the same occupation. In general, the performance of employees believed tobe influenced by compensation, motivation and commitment from employees themselves, suchperformance will ultimately have an impact on organizational performance. To determinewhether the compensation, motivation, and organizational commitment have a significanteffect on the performance of the accounting employee on manufacturing companies producingfootwear in Surabaya, the research was conducted. The method thats used in this studyis the multiple linear regressions. Data thats used in this study is the result of primary dataquestionnaire with 32 respondents. The result shows that that motivation significantly influenceemployee performance, compensation and organizational commitment whereas no significanteffect on employee performance.